Estudo neuroanatômico do éncefalo bovino por ressonância magnética - Bueno, Laís Melicio Cintra [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Magnetic resonance imaging (MRI) has revolutionized veterinary medicine in the field of diagnostic imaging. Technology currently considered as the most sensitive method for the analysis of soft tissues such as the brain, bypassing the other diagnostic methods. This technology is based on nuclear magnetic resonance phenomenon that occurs when atomic nuclei with magnetic properties present in the body of humans and animals are subjected to an intense magnetic field. Its advantages in the production of brain images are noninvasive, is characterized by high resolution, high contrast, two-dimensional plane, grayscale, produces less artifacts and does not use ionizing formats of electromagnetic energy. Presents no risk to the patient and proven professionals submitted to the examination. Although MRI is the preferred technique to examine the brain, this information is scarce when related brain anatomical features in domestic ruminants. The purpose of this study is to describe normal bovine brain neuroanatomy (Bos taurus domesticus) order correlations with normal magnetic resonance imaging findings. This research is of importance because, normal neuroanatomical definition will provide accurate diagnosis of different diseases traumatic, vascular, infectious, degenerative or neoplastic, among other. Brains were carefully extracted and fixed for conventional anatomical cuts. Transverse and sagittal MRI were obtained from two fresh heads of adult cattle at 0.25T ESAOTE Vet-MR GRANDE device through the coil C-shaped coil in the sequences performed in the transverse plane T1 and T2 sagittal, T1 and T2 and the plan dorsal. After the acquisition, images were transferred in DICON format for Synapse® PACS application and analyzed by an observer at ClearCanvas Workstation program. The most clinical interest neuroanatomical structures were set according to the methodology of Yokoshi & Rohen and named after neuroanatomy texts

A imagem originada por ressonância magnética (MRI) revolucionou a medicina veterinária na área de diagnóstico por imagem. Tecnologia considerada atualmente como a metodologia mais sensível para análise de tecidos moles, como o encéfalo, ultrapassando os demais métodos diagnósticos. Essa tecnologia fundamenta-se no fenômeno da ressonância magnética nuclear que ocorre quando os núcleos atômicos com propriedades magnéticas presentes no corpo dos humanos e dos animais são submetidos a um campo magnético intenso. Suas vantagens na produção de imagens do encéfalo são método não invasivo, caracteriza-se por alta resolução, intenso contraste, plano bidimensional, em tons de cinza, produz menos artefatos e não utiliza formatos ionizantes de energia eletromagnética. Não apresenta riscos comprovados para o paciente e profissionais submetidos ao exame. Apesar da MRI ser a técnica de eleição para examinar o encéfalo, essas informações são escassas quando relacionadas com características anatômicas encefálicas em ruminantes domésticos. A finalidade deste estudo é descrever neuroanatomia encefálica bovina (Bos taurus domesticus) normal objetivando correlações com achados normais de ressonância magnética. Este trabalho reveste-se de importância pois, a definição neuroanatômica normal propiciará diagnósticos acurados de diferentes enfermidades traumáticas, vasculares, infecciosas, degenerativas ou neoplásicas, dentre outras Os cérebros foram cuidadosamente extraídos e fixados em formol para cortes anatômicos convencionais. Cortes transversais e sagitais de MRI foram obtidos de duas cabeças frescas de bovinos adultos pelo aparelho ESAOTE 0.25 T Vet-MR GRANDE através da bobina C-shaped coil nas sequências efetuadas no plano transversal T1 e T2 no plano sagital, T1 e T2 e no plano dorsal. Após a aquisição, imagens foram transferidas em formato DICON para o aplicativo...
Neuroanatomical study of bovine brain using magnetic resonance imaging
Keywords: Bovino; Ressonância magnética; Biotecnologia animal; Neurologia veterinaria; Cerebro - Radiografia; Veterinary neurology; Magnetic resonance